(untitled) (Fiep Bulletin - online, 2013)
The present study aimed to continue a survey conducted in 2011 with students enrolled in the 8th grade of elementary school at a public school in Campo Grande - MS. We conducted tests with the same class, as today the 9th grade (2012) performing a data comparison with the results obtained thus evaluating the level of physical fitness related to adolescent health. This is a longitudinal survey, being a descriptive quantitative survey. The research was conducted with individuals of both sexes, with ages 13-15 years old; in 2011 the test was performed by students enrolled in the 8th grade and consisted of 57 students, being 27 male and 30 female students. The test was repeated with the same classroom today 9th grade (2012) and it consisted of 59 students, 29 male and 30 female students both in the vespertine period. In the evaluation, were performed the height measure, body mass index (BMI), run / walk for nine minutes covering the largest possible distance (aerobic capacity), sit and reach test to measure joint mobility (flexibility) and make the largest number of repetitions abdominal within one minute to check abdominal resistance. Study results revealed that the level of physical fitness had major changes from one year to the other mainly among males. The female subjects showed better levels of fitness.